Coexistence of self- and interpenetration in two (3, 6)-connected porous coordination polymers. Issue 44 (19th October 2016) - Yao, Qingxia; Fan, Yerong; Wang, Zhan; Duan, Wenzeng; Wang, Suna; Li, Yunwu; Li, Dacheng; Zhang, Qingfu; Du, Yuchang; Dou, Jianmin
Abstract : Two self-penetrating coordination networks are mutually interpenetrated to give a soft porous entanglement, which can be used for the selective detection of nitrobenzene through fluorescence quenching. Abstract : Two isostructural (3, 6)-connected porous coordination polymers topologically featuring both self- and interpenetration have been successfully synthesized. The porous material shows a reversible crystalline-to-amorphous transition associated with the removal and recapture of guest molecules. Particularly, the porous material demonstrates selective detection of nitrobenzene through fluorescence quenching.